Pathways of disadvantage and smoking careers: evidence and policy implications. (11th August 2006) - Graham, Hilary; Inskip, Hazel M; Francis, Brian; Harman, Juliet
Abstract : Objectives: To investigate in older industrialised societies (a) how social disadvantage contributes to smoking risk among women (b) the role of social and economic policies in reducing disadvantage and moderating wider inequalities in life chances and living standards. Methods: Review and analysis of (a) the effects of disadvantage in childhood and into adulthood on women's smoking status in early adulthood (b) policy impacts on the social exposures associated with high smoking risk. Main results: (a) Smoking status—ever smoking, current smoking, heavy smoking, and cessation—is influenced not only by current circumstances but by longer term biographies of disadvantage (b) social and economic policies shape key social predictors of women's smoking status, including childhood circumstances, educational levels and adult circumstances, and moderate inequalities in the distribution of these dimensions of life chances and living standards. Together, the two sets of findings argue for a policy toolkit that acts on the distal determinants of smoking, with interventions targeting the conditions in which future and current smokers live. Conclusions: An approach to tobacco control is advocated that combines changing smoking habits with reducing inequalities in the social trajectories in which they are embedded. Policies to level up opportunities and living standards across the lifecourse should be championed as part of an equity oriented approach to reducing the disease burden of cigarette smoking.